Cultivated and constructed memory in the Bonaria cemetery in Cagliari - Malone, Hannah (My University, 2021)
A cemetery is a monument, or rather a collection of monuments, which serves to generate, reinforce, and perpetuate memories. However, that function cannot be easily defined in that it is complex, dynamic, and multifaceted. A cemetery is a vessel for many memories, not only of the recent dead, but also of cities, communities, and cultures. Moreover, the perpetuation of memories is an on-going and evolving process.
Gardening Time
PUBLISHED